Aprendizaje cooperativo y enseñanza del inglés como idioma extranjero - Pérez, John; Idarraga-Gallego, María Fernanda; Quintero-Torres, Fredy Alonso (Colombian Applied Linguistics Journal, 2024)
This article aims to explore the understandings and of secondary education teachers and students regarding cooperative learning, and to examine how it contributes to and benefits the teaching and learning of a foreign language. The study employs a mixed-methods approach, incorporating narrative methods and emphasizing content analysis through a lexicometric test. The results reveal that strategies derived from cooperative learning are widely, diversely, and frequently applied. However, the study also concludes that there is a need to strengthen pedagogical intentions and the application of cooperative strategies. This enhancement should be informed by theoretical insights and various mediations to better support the dynamics of teaching and learning.